Peran Job Crafting pada Work Engagement Guru Yayasan “X” di Kota Bandung - Jacqueline Tjandraningtyas; Meta Dwijayanthy; Michelle Ratna Salim (Universitas Kristen Maranatha, 2025)
Fulfilling job demands and work responsibilities requires various resources, both from the teachers themselves and from the organization. Effective management of job resources can help teachers meet job demands. The JD-R (Job Demands-Resources) model is aimed at increasing teachers' work engagement with their profession. This study seeks to examine the role of job crafting in relation to work engagement among teachers. The theories used are the work engagement theory by Bakker, et al. (2008), and the job crafting theory by Tims and Bakker (2010, 2012). The study focuses on teachers who have worked for at least one year at Foundation